Apricot attenuates oxidative stress and modulates of Bax, Bcl-2, caspases, NF?-B, AP-1, CREB expression of rats bearing DMBA-induced liver damage and treated with a combination of radiotherapy - Karabulut, Aysun Bay; Karadag, Nese; Gurocak, Simay; Kiran, Tugba; Tuzcu, Mehmet; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2014)
We evaluated the ability of apricot to attenuate apoptosis and oxidative stress developed during the process of 7,12-dimethylbenz[a]anthracene (DMBA) and radiotherapy in the liver of rats bearing liver damage. Fifty female Wistar rats were divided into 7 groups; (i) normal control rats; (ii) rats fed with standard diet with apricot (20%), (ii) rats fed with standard diet and administrated 6 gray radiotherapy with Co 60 device applied to a single fraction, (iv) rats fed with standard diet and administered intraperitoneally DMBA (20 mg/kg), (v) rats fed with standard diet and administered DMBA and 6 gray radiotherapy, (vi) rats fed with standard rat diet and administered DMBA and supplemented apricot, (vii) rats fed with standard diet supplemented apricot administered DMBA and radiotherapy (RT) for 6 weeks. Expression of Bax, caspase 3, and glutathione activity decreased in the liver but liver expression of NF-kappa B, AP-1, CREB, Bcl-2 and ALT, AST, 5'NT, MDA, NO levels increased in DMBA-induced liver damage rats. In conclusion, the results suggest that apricot supplementation and irradiation given in combination, offer maximum protection against DMBA-induced hepatic carcinogenesis. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 7,12-Dimethylbenz[a]anthracene; Liver damage; Apricot; Radiotherapy; Apoptosis; Oxidative stress